Pertanggungjawaban Pidana Beneficial Owner Saham dalam Tindak Pidana Perpajakan (Studi Putusan Pengadilan Tinggi Medan Nomor 66/Pid.Sus/2018/PT.Mdn) - Tri Yuwandani Hayuningtyas; Bismar Nasution; Budiman Ginting; M Ekaputra (Universitas Medan Area, 2022)
This study aims to determine the purpose of establishing a Limited Liability Company, namely to limit the owner's liability in the event of a financial loss. Shareholders are only responsible for the amount of shares they own. However, the development of piercing the corporate veil, the limitation of liability can be penetrated, for example due to fraud, inadequate capital, failure to fulfill the formalities of company establishment, and abuse of power in a company due to the domination of one or more shareholders. This study uses a normative legal research method that is descriptive analytical. The results of the study indicate that the liability of the beneficial owner for tax crimes based on a study of the Medan High Court Decision No. 66/Pid.Sus/2018/PT.Mdn was declared legally and convincingly guilty of committing a crime in the taxation sector in Article 39 paragraph (1) letter c in conjunction with Article 43 paragraph (1) of the Law of the Republic of Indonesia Number 16 of 2000 concerning Second Amendment to the Law of the Republic of Indonesia Number 6 of 1983 concerning General Provisions and Tax Procedures. Regarding the imprisonment substitute sentence, it is not regulated in the KUP Law as lex specialis nor in the Criminal Code as lex generalis. The imposition of a fine that can be replaced with a substitute sentence for imprisonment in this decision basically gives the defendant a choice, whether he wants to pay a fine or undergo a substitute sentence in the form of imprisonment